Factors associated with attachment in international adoption - Bartel, Teresa Maria Campbell (Kansas State University, 2005)
As the number of adoptable infants within the U.S. has declined, many families have chosen to adopt internationally. According to the U.S. Department of State, for the 2002 fiscal year 19,139 immigrant visas were issued to orphans coming into the U.S. A majority of these adopted children came from China, South Korea, Romania and Russia. Previous studies have found attachment problems in some adopted populations in early childhood. However, a majority of studies have focused on other problem areas for older adopted children. The purpose of this study was to investigate the factors associated with attachment in children adopted from these four countries in early childhood. All of the agencies within the U.S. that provided adoption services to these four countries were contacted through letters describing the study. The agencies that agreed to participate contacted potential participants directly through a form letter describing the study and that contained a website address for them to visit. At this website address, the potential participants were asked to fill out a survey regarding their adoption experience. A total of 242 families who had adopted children who were currently between one and six years of age agreed to participate in the study. Results indicated that secure attachments with their adoptive families were more likely in instances where the parenting style was authoritative, there was a positive emotional reaction from the parents on the day of adoption, the parents received strong social support, there were fewer health/developmental problems at arrival for the adopted child, there were fewer health/developmental services needed for the adopted child, the child spent more months in the adoptive home at the time of the survey and the parent spent more time with child before returning to work. Also, results indicated that adopted children displayed more indiscriminately friendly behavior the more months spent in the adoptive home at the time of the survey and the more time the child spent in the institution. The findings of this study support and extend previous research done on this topic while simultaneously opening up new avenues for international adoption research to explore. The findings of this study also provide useful information for adoption agencies to incorporate in their training of social workers and informing parents of the factors associated with developing secure attachments with their internationally adopted children.
Keywords: International adoption; Attachment; Psychology, Developmental (0620); Sociology, Individual and Family Studies (0628)